Kelayakan Usaha Peternakan Domba Padukuhan Wonosobo, Sardonoharjo, Ngaglik, Sleman, DI Yogyakarta - Sulistio, Joko; Budiawan , Nagusta Tri (Universitas Islam Indonesia, 2024)
Increased public consciousness regarding the significance of meeting nutritional needs, such as calories and animal protein, causes the demand for food from livestock to increase, one of which is sheep meat. The rising population contributes to a continual increase in the demand for sheep. This study aims to assess the viability of the livestock industry in the Sardonoharjo Sub-Village of Wonosobo, Ngaglik Kapanewon, Sleman Regency. This study uses different models in animal husbandry, namely the first (X1) sheep farming in general and the second (X2) farming with farmer partners. Then the investment parameters used to determine a feasible and profitable business are the R/C Ratio , the B/C Ratio , and the BEP. Analyzing the feasibility of a sheep business through two distinct models reveals that the farming model involving farmer partners (X2) proves to be more lucrative over three years. With a higher R/C Ratio and B/C Ratio value, it is more feasible, as well as a lower BEP price, so that it breaks even faster and is more stable against price changes compared to model X1.